Drivers of adolescents’ food choices: exploring the influence of the school food environment - Karunanayaka, M.M.S.; Thalwaththa, T.; Rajapaksha, I.P.; Madurangi, A.P.H.; Indramali, O.S.; Perera, T.; Mohotti, J.; Hunter, Danny; Silva, K.D.R.R. (2024)
Presented at the 2024 Delivering for Nutrition in South Asia Conference. Adolescence is one of the critical stages of life as dietary behaviors developed during this period are likely to be carried into adulthood. Therefore, this study aimed to identify key drivers of food choices among adolescents, particularly within the school food environment where they spend a substantial amount of their time. A mixed-methods design was employed across 18 schools in two neighborhood districts in Sri Lanka. Data collection involved surveys, focus group discussions (FGDs), and in-depth interviews (IDIs). A survey was administered to 400 students aged 12-14, capturing data on their food choices and practices while at school. Additionally, 12 FGDs with 120 students and 15 IDIs with principals were conducted, using semi-structured guides to explore the influence of different dimensions of the school food environment (SFE) on adolescents' food choices. The qualitative data were analyzed using thematic analysis to identify key themes and descriptive statistics were used to analyze quantitative data. The survey results revealed that adolescents' food choices were primarily driven by taste (92%), price (88%), and appearance (81%), leading them to buy unhealthy food from school canteens and nearby food outlets. FGDs highlighted individual food preferences, peer influence, food advertisements, and media exposure as factors affecting their food choices. IDIs with principals identified four key themes affecting students' eating habits within the SFE: (i) individual factors such as food desirability and affordability, (ii) social factors including peer and home influence, (iii) physical environment factors including the availability of school canteens, food gardens, and nearby food outlets, and (iv) macro-level factors such as school policies and marketing strategies. The food drivers within the SFE are influenced by a nexus of factors. A thorough investigation into these drivers is necessary to address the issues associated with unhealthy diets among adolescents. Future research should implement and evaluate specific changes in SFE to identify effective strategies to change adolescents' dietary behaviors. The work showcased in this presentation was supported by a grant from the Nestlé Foundation, Lausanne, Switzerland.